2009
DOI: 10.1182/blood-2009-03-209205
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of human megakaryocytes to high shear rates accelerates platelet production

Abstract: Platelets originate from megakaryocytes (MKs) by cytoplasmic elongation into proplatelets. Direct platelet release is not seen in bone marrow hematopoietic islands. It was suggested that proplatelet fragmentation into platelets can occur intravascularly, yet evidence of its dependence on hydrodynamic forces is missing. Therefore, we investigated whether platelet production from MKs could be up-regulated by circulatory forces. Human mature MKs were perfused at a high shear rate on von Willebrand factor. Cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
142
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(151 citation statements)
references
References 52 publications
9
142
0
Order By: Relevance
“…A major limitation of twodimensional liquid cultures has been their inability to account for three-dimensional BM composition and stiffness, directionality of proPLT extension, and proximity to venous endothelium. 15,24,25 Alternatively, intravital microscopy studies have provided physiologically accurate examples of proPLT production, however, poor resolution and limited control of the microenvironment has prohibited detailed study of how the BM microenvironment contributes to PLT release. 11,15 Nakagawa et al 50 recently published 3 bioreactor designs to produce human PLTs at scale from hiPSC-and ESC-derived MKs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A major limitation of twodimensional liquid cultures has been their inability to account for three-dimensional BM composition and stiffness, directionality of proPLT extension, and proximity to venous endothelium. 15,24,25 Alternatively, intravital microscopy studies have provided physiologically accurate examples of proPLT production, however, poor resolution and limited control of the microenvironment has prohibited detailed study of how the BM microenvironment contributes to PLT release. 11,15 Nakagawa et al 50 recently published 3 bioreactor designs to produce human PLTs at scale from hiPSC-and ESC-derived MKs.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence that cell-cell contacts, 22,23 ECM composition 19,20 and stiffness, 21 vascular shear stress, 24,25 pO2/pH, 51,52 soluble factor interactions, 22,53 and temperature 54 contribute to proPLT formation and PLT release have suggested that recapitulating key components of BM and blood vessel microenvironments within a three-dimensional microfluidic culture system is necessary to achieve clinically significant numbers of functional human PLTs. Our microfluidic bioreactor design expands control and resolution of the microenvironment, and has allowed us to drastically improve the time to PLT release (from 18 hours down to 2 hours) and more For personal use only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CD41 1 subpopulation is short lived, preactivated, weakly reactive, and underincorporated into thrombi. EV-PLPs generated in bioreactors [51][52][53][54][55] have been described and such high-throughput devices are clearly needed to achieve largescale EV-platelet production. Like infused EV-megakaryocytes, they would have the advantage of producing mostly young platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Blood shear stress contributes to the shedding of PPs Dunois-Lardé et al, 2009;Thon et al, 2010); however, whether additional signals are required for efficient PP shedding was completely unknown. In this study, we show that hydrodynamic forces alone are not sufficient to allow the release of new platelets from MK PP extensions.…”
Section: S1p Navigates Pp Extensions Into Bm Sinusoids and Initiates mentioning
confidence: 99%